Effectiveness of the new formulation of GNP/SA hybrid conductive ink on torsion/bending cyclic loading - Hussin, Hazril Hisham (2024)
In a dynamic era characterized by the integration of innovation and technology, hybrid conductive ink has emerged as a powerful catalyst in the production of flexible electronic devices. It also opens up new opportunities to advance electronic printing technology. However, there are challenges in realizing it, namely in terms of formulating a suitable ink material for that purpose. Materials such as graphene nanoplatelets (GNP), which are carbon-based, become fillers in polymer composites together with silver flakes (Ag), planning a good combination with silver acetate (SA) to produce a new formulation of conductive hybrid ink. This research aims to study the characteristics and uses of GNP hybrid conductive ink when mixed with organic solvents and cured at 250°C. Several aspects have been studied as a research goal in terms of formulating a new GNP hybrid conductive ink formulation and further, comparing the characteristics of the new conductive ink formulation against the mechanical, electrical and morphological properties of the flexible substrate. The optimal formulation process of the hybrid conductive ink is important in ensuring its level of resistivity during cyclic testing using the Two-Point-Probe measurement technique. The evaluation of electrical and mechanical conductivity is started by carrying out a cyclic test on the sample and comparing it to the baseline, which is not subjected to the test. After the cyclic tests of torsion and bending are conducted, shear stress tests are also conducted to determine the mechanical properties. The reliability of the new formulation of conductive ink was also evaluated. After the cyclic and baseline tests, a comparative analysis of the GNP hybrid revealed no significant changes in the tested sample's resistivity. The total average resistivity of the sample was 1.99E-05 Ω.m at baseline, and the lowest average for torsion was 2.02E-05 Ω.m and for bending, 2.41E-05 Ω.m. The higher shear stress values (MPa) for samples cured at 5 hours indicate a better result with an average of 57.36 MPa. The findings in this research show that the hybrid formulation of GNP in conductive ink can improve its electrical conductivity performance with an average improvement of 42.58% for both torsion and bending tests. This provides valuable insights, and pave the way for future improvements in conductive ink formulations that can be utilized in various flexible electronic applications.